Crimes Against Women in India - Dr. Vinod Kumar (Studies in Law and Justice, 2023)
Crime against women arises as a direct result of violence against them. The issue of violence against women has been the most important issue of women’s movement in India since 1974-75. First it was the ever-increasing number of ‘dowry deaths’. Then, from 1980, different rape cases for grounded rape as a major issue. This was followed by the revival of the ancient custom of Sati. The limelight next shifted to female infanticide as well as female foeticide. There was the advent of ultra modern medical forms of violence against females through bio medical practices, such as amniocentesis. Domestic violence, sexual harassment at work Crimes against women, like all other acts of violence and crimes, have to be seen in the social, economic and political contexts of power relations. It occurs within class and caste because of patriarchal social relations under which male power dominates. A narrow view of crime and violence sees it merely an act of illegal, criminal use of physical force. But a broader view includes exploitation, discrimination, upholding of unequal economic and social structures, the creation of an atmosphere of terror, threat or reprisal and all forms of religio-cultural and political violence. This research paper will concern with the crimes identified in the Indian Penal Code (IPC) and also those which come under Special Law (SL).